LEGALITAS WEBSITE KOMERSIAL - Hayat, Cynthia; Hutapea, Afrido V. (Teknik dan Ilmu Komputer, 2013)
Transactions over the internet are uncontrolled both from the legal clarity and trade tax aspects. The increasing number of deception and fraud cases emphasizes the importance of a system or a governing body to manage online trade. This system or body should issue permits for or approve the legitimacy of commercial websites. The online transactions are expected to be better organized and legally existed. The government can also apply trade tax for online transactions. The website legality will increase customersâ confidence to do online transactions, reduce the crime rate, and increase the countryâs income through online trade tax. Â Keywords:Â  legality, legality of commercial website, EC-trust